FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU ORANG TUA DALAM MEMBERIKAN PENDIDIKAN KESEHATAN REPRODUKSI PADA ANAK USIA DINI DI KECAMATAN X KOTA PADANG - Nursya, Febriyanti; Yuliza, Wilda Tri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Limited access to information on reproductive health results in children receiving inaccurate information. Reproductive health education should be provided to children from an early age, and it is the parents' duty or obligation to provide it to their children to reduce acts of sexual violence against children. In 2024, there were 89 cases of child abuse in Padang City, with the district with the highest number of recorded cases of sexual abuse against children aged 1-10 years being X District. The purpose of this study was to determine the factors related to parental behavior in providing reproductive health education to early childhood in X District in 2025. The study design was cross-sectional. The population was parents with early childhood children with a sample size of 64 people. Data collection used a questionnaire. Data analysis included univariate and bivariate analyses. The results showed that most respondents had provided reproductive health education to early childhood (56.3%), high knowledge (62.5%), positive attitudes (65.6%), and exposure to information media (59.4%). Bivariate analysis showed a significant relationship between knowledge (p=0.002), attitude (p=0.010), and dissemination of information media (p=0.015) with parental behavior in providing reproductive health education.Keywords : Children, Sexual Violence, Reproductive Health